2015
DOI: 10.1016/j.jpor.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of crown restoration retrofitting to existing clasps using CAD/CAM: Fitness accuracy and retentive force

Abstract: When a crown restoration must be remade to retrofit an existing clasp, CAD/CAM fabrication can be recommended so that both appropriate fitness and retentive force are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 32 publications
(39 reference statements)
0
8
1
Order By: Relevance
“…significantly higher retentive forces for RPDs compared with conventionally fabricated restorations. 33 In addition, the data gathered from the present study do not support data from clinical reports that used intraoral scanners to capture and fabricate retrofitted crowns. [30][31][32] The present study was limited as only 4 predetermined locations were used to evaluate the reproduction of the external surface contour.…”
contrasting
confidence: 60%
See 1 more Smart Citation
“…significantly higher retentive forces for RPDs compared with conventionally fabricated restorations. 33 In addition, the data gathered from the present study do not support data from clinical reports that used intraoral scanners to capture and fabricate retrofitted crowns. [30][31][32] The present study was limited as only 4 predetermined locations were used to evaluate the reproduction of the external surface contour.…”
contrasting
confidence: 60%
“…The successful use of the CAD-CAM technology has been reported in the chairside production of survey crowns fitted to the existing RPDs. [29][30][31][32] However, similar to laboratory CAD-CAM systems, 33 a more critical evaluation of chairside technologies is needed in the context of reproduction of existing survey crowns.…”
mentioning
confidence: 99%
“…Yoon and Chang reported that a disadvantage of their technique is that it only produced a ceramic crown, which may be suitable for only a PRDP tooth‐supported design and may not be suitable for distal extension designs due to the risk of fracture. This report modifies previously reported techniques by using cast gold material, eliminating the risk of restoration fracture when used as a distal abutment. The technique also allows for more conservative cast gold tooth preparation, in comparison to the amount of tooth reduction required for a ceramic restoration.…”
Section: Discussionmentioning
confidence: 70%
“…With computer‐aided design/computer‐aided manufacturing (CAD/CAM) technology gaining more popularity, Marchack et al reported duplicating the waxing tooth design to fabricate a ceramic survey crown to fit an existing PRDP. The approach was later modified to include scanning pretreatment models and waxing to fabricate a survey crown . Patel used a similar technique, using the “biogeneric copy” of the CEREC system to fabricate a ceramic survey crown.…”
mentioning
confidence: 99%
“…Recently, computer‐aided engineering has been tried for implant planning and the fabrication of prosthetic appliances . Complete denture construction using computer‐aided design and computer‐aided manufacturing (CAD/CAM) can provide better fit by reducing polymerization distortion and thus can possibly produce an acceptable complete denture prosthesis using digital techniques …”
mentioning
confidence: 99%